Contextual Video: Critical Thinking-Based Learning Media in The Implementation of Curriculum 2013 (Dinamika Pendidikan, 2017)
This research aims to know the development of critical thinking-based contextual video media on the subject matter of economic issues and how to overcome it, and to find out the feasibility of critical thinking-based contextual video media and student's response towards the critical thinking-based contextual video media. The implementation of curriculum 2013 cannot be separated from the government's expectation that learners have good soft skills.The desired skills are 21st century skills known as 4C: creative, critical thinking, communicative and collaborative. These skills emphasize the soft skills implemented in daily life, learners understand the importance of these skills. The existence of contextual video helps to simplify the process; learners are brought into real life. The learning is more implementative. Critical thinking is the basis of video, the video making process is made in such a way so that the learners understand the material by temselves from analyzing every plot of video. The video material is about economic issues and how to overcome them. This research was Research and Development (RD). The development cycle used Thiagarajan, Semmel and Semmel’s model or 4-P model that are defining, designing, developing, and deploying. However, this study was only up to the stage of development. The place of this study was in Vocational High School Muhammadiyah 1 Babat. The result of the research stated that based on media feasibility test from the material expert, it is very feasible with the percentage of 80,44% and the media learning expert assessed very well with the percentage of 88,82%. And the result of class X students’ response to media is very good with the percentage 83, 64%. So it is concluded that contentxtual video media is feasible to be used as a learning media.